Inadequately marketing our brand: Medical student awareness of acute care surgery. Issue 5 (November 2015) - Montgomery, Stephanie C.; Privette, Alicia R.; Ferguson, Pamela L.; Mirdamadi, Meena; Fakhry, Samir M.
Abstract : BACKGROUND: Despite focused national efforts to promote acute care surgery (ACS), little is known about medical student awareness of ACS as a career choice. The impending shortage of general surgeons emphasizes the need to increase interest in this comprehensive surgical specialty. The goal of this study was to determine whether students would be more likely to consider choosing ACS if they were aware of the specialty and its benefits. METHODS: A survey was distributed electronically to medical students at our institution, a Level I trauma center with an active ACS service. The survey asked questions regarding specialty choice and factors that were used in making that decision. Also included were questions regarding their familiarity and affinity for ACS. RESULTS: The survey was returned by 518 students. Each medical school year was proportionately represented. Twenty-one percent of the students reported surgery as their career choice; however, women were half as likely to choose surgery as men. When asked to define ACS, 23% of all students gave the correct response. Only 8.9% of the students in the preclinical years correctly defined ACS. Even in the clinical years, 54% were unaware of ACS as a specialty. Students reported that the top factors that influenced their choice were controllable lifestyle, predictable schedule, and a positive medical school role model. When asked to identify what would make ACS appealing, a 50-hour work week was deemed most influential. When given the definition of ACS with approximate pay and on-call hours, 41.5% of the students and 75% of those interested in surgery would be likely to choose ACS as a career. CONCLUSION: This study highlights that awareness of ACS as a specialty is lacking. This may reflect inadequate marketing of our "brand" both locally and nationally. Focused efforts at familiarizing students with ACS and increased role modeling may increase interest in ACS. Abstract : Supplemental digital content is available in the text.